2015
DOI: 10.1002/app.42075
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of carbon nanotubes and carbon black on the fracture and fatigue resistance of natural rubber composites

Abstract: The quasi-static fracture and dynamic fatigue behaviors of natural rubber composites reinforced with hybrid carbon nanotube bundles (CNTBs) and carbon black (CB) at similar hardness values were investigated on the basis of fracture mechanical methods. Mechanical measurement and J-integral tests were carried out to characterize the quasi-static fracture resistance. Dynamic fatigue tests were performed under cyclic constant strain conditions with single-edged notched test pieces. The results indicate that synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…Recently, features such as crystallinity, shape anisotropy, density, surface area and oil absorption of CNT, a nanosized graphite and CB have been comparatively investigated [23,24]. Moreover, studies on synergistic effects have been performed, both in thermoplastic [15] and elastomeric matrices [24][25][26][27]. In particular, in poly(1,4-cis-isoprene) as the polymer matrix, the synergistic effect on the mechanical…”
Section: Introductionmentioning
confidence: 99%
“…Recently, features such as crystallinity, shape anisotropy, density, surface area and oil absorption of CNT, a nanosized graphite and CB have been comparatively investigated [23,24]. Moreover, studies on synergistic effects have been performed, both in thermoplastic [15] and elastomeric matrices [24][25][26][27]. In particular, in poly(1,4-cis-isoprene) as the polymer matrix, the synergistic effect on the mechanical…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in the literature that CB helps CNT dispersion in a polymer matrix [71][72][73][74]. As already commented, synergistic effects on mechanical reinforcement have been reported for hybrid filler systems formed by nanometric and nano-structured carbon allotropes, such as CNT and CB [17,24,[27][28][29][30][31]. Graphs in Figure 5a and Figure 6 and data in Tables 4 and 5 reveal the much larger reinforcing ability of CNT.…”
Section: Composites Based On Sp 2 Carbon Allotropesmentioning
confidence: 62%
“…In most studies, CB and carbon nanofillers have been separately investigated and only recently [25,26] crystallinity, shape anisotropy, density, surface area and oil absorption of CNT, a nanosized graphite and CB have been compared. Interestingly, synergistic effects on mechanical reinforcement, between CB and nanofillers, have been shown in both elastomeric [17,24,25,[27][28][29][30] and thermoplastic [31] matrices. Previous works by the authors highlighted that the mechanical reinforcement of an elastomer matrix promoted by hybrid fillers is not the result of the simple addition of reinforcing effects by each single filler [25,30].…”
Section: Introductionmentioning
confidence: 99%
“…The J ‐integral tests were conducted to measure the resistance of quasi‐static crack initiation and propagation of CNTs/CB/SBR composites. Its detailed testing process has been presented in our previous works . Briefly, SENT (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Tremendous attention has been attracted in the fields of hybrid filler system, such as spherical CB and fibrous CNTs , which revealed that partial replacement of CB with small amounts of CNTs induced synergistic effects on the mechanical, thermal, and electrical properties. For the hybrid filler networks, unequal replacement (low amounts of CNTs replacing high amounts of CB) might lead to a better synergistic effect than equal replacement . To the best of our knowledge, however, the fracture resistance of hybrid CNTs and CB filled SBR composites, especially the influence of hybrid filler networks on strain amplification and distribution near the crack tip and its relationship with fracture resistance, are rare and of great interest.…”
Section: Introductionmentioning
confidence: 99%